2021
DOI: 10.1108/apjml-10-2020-0715
|View full text |Cite
|
Sign up to set email alerts
|

Islamic bank trust: the roles of religiosity, perceived value and satisfaction

Abstract: PurposeThis study aims to examine the relationship between trust and its antecedents, i.e. customer satisfaction, perceived value and religiosity. The moderating roles of religiosity on the relationships between perceived value, satisfaction and trust also have been investigated in this study.Design/methodology/approachThis research has carried out in West Sumatra Indonesia. The respondents of this study are Islamic bank customers from five areas in West Sumatra Indonesia. Data have been collected through Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 55 publications
5
23
0
7
Order By: Relevance
“…Consumers are more likely to trust livestream shopping if they believe the technology offers less risk, more benefits, and fewer restrictions. The results are consistent with previous research (7,39,40). However, the result for significant positive effect of perceived susceptibility and perceived severity on trust is contrary to previous studies, such as Yuen et al (7), who found a significant negative effect of perceived safety threat on consumers' trust about the cruise services.…”
Section: Structural Model Assessmentsupporting
confidence: 88%
See 1 more Smart Citation
“…Consumers are more likely to trust livestream shopping if they believe the technology offers less risk, more benefits, and fewer restrictions. The results are consistent with previous research (7,39,40). However, the result for significant positive effect of perceived susceptibility and perceived severity on trust is contrary to previous studies, such as Yuen et al (7), who found a significant negative effect of perceived safety threat on consumers' trust about the cruise services.…”
Section: Structural Model Assessmentsupporting
confidence: 88%
“…In this context, perceived barriers would include an individual's perception of the expense and difficulty of taking health precautions (31). Existing research has shown that perceived barriers can significantly reduce consumer trust (39) while, according to Abror et al (40), perceived benefits is an important antecedent of consumer trust. Chen and Chang (41) also posited that there is a positive association between perceived benefits and consumer trust because a high degree of perceived benefits may boost post-purchase product confidence.…”
Section: Behavioral Evaluation: Perceived Benefits and Perceived Barriersmentioning
confidence: 99%
“…Studi sebelumnya mengungkapkan bahwa religiositas setiap orang berbeda-beda karena sifat dan perilaku setiap individu dalam beragama juga berbeda-beda (A.N & Sutarso, 2021). Beberapa penelitian membuktikan adanya pengaruh religiositas terhadap perilaku seseorang termasuk kepuasan (Joshanloo & Weijers, 2016), loyalitas (Albaity & Rahman, 2021), dan kepercayaan (Abror et al, 2022).…”
Section: Variabel Utautunclassified
“…Adaptive selling behavior and customer satisfaction Customer satisfaction is essential to customers in every service encounter (Abror et al, 2021;Sabir, 2020;Chan et al, 2016;Amenuvor et al, 2019b). Customer satisfaction is acknowledged when a salesperson meets a customer's expectation in a service encounter (Crosby et al, 1990).…”
Section: Customer-related Outcomes Of Adaptive Selling Behaviormentioning
confidence: 99%